Public accounting firms views on characteristics of its' potential employees / Ros Norita Abd Samad ... [et al.] - Abd Samad, Ros Norita; Muda, Salwa; Che Hassan, Anita; Awang, Yunita; Yusoff, Rohana; Abdul Aziz, Inayah (2012)
Accounting graduates must equip themselves with numbers of characteristics as required by their potential employers. This study identifies the characteristics sought in new accounting employees by public accounting firms. Questionnaires were distributed to employers of Public Accounting Firms and UiTM graduating accounting students. The result shows that students are in agreement with employers' opinions regarding the importance of work quality and work attitude. However, there is a difference on the importance of skills such as ability to work in team, looking for ways to improve job performance, presentation skills and planning skills. Students seem to undervalue the importance of these skills as compared to employers. In future, it would be interesting to incorporate a wider range of graduating accounting students and employers groups.